Do the Pragmatic Program Budgeting Help Practitioners Apply Performance-Based Budgeting More Effectively? The World Bank’s New Pragmatic Program Budgeting: Does It Make Budgeting More Effective? - Yudisatria, Aria (Journal of Public Administration and Policy Issues, 2022)
The adoption of performance-based budgeting has become increasingly popular among governments seeking to enhance resource efficiency and accountability. While this approach provides flexibility and prioritization in budget allocation, its implementation remains challenging due to complexities in planning, management, and control. The World Bank’s guidance on New Pragmatic Program Budgeting (PPB) addresses these challenges by offering three pragmatic solutions: controlling budgets at the program or subprogram level, recording all financial transactions, and harmonizing budget programs with administrative structures. This paper evaluates the effectiveness of these solutions and highlights potential gaps in their implementation, including difficulties in linking inputs, outputs, and outcomes, as well as agency-principal issues.